Report on amendment of the law as to ruined houses in towns - SSISI (Statistical and Social Inquiry Society of Ireland, 1876)
The Council of the Charity Organisation Society of London having entered into the subject of the defective state of houses in London, and had a committee of inquiry, and having made representations to the government on the subject, the Committee have had under their consideration the subjoined proposal of Dr. Hancock, to extend the Scotch law as to ruined houses to England and Ireland.
Twenty ninth session ? 1875/1876
Keywords: Charity organizations; Poverty; Ruined houses; Derelict housing; 314.15